A Comprehensive Analysis: Perception, Innovativeness, and Intention of Consumers As Determinant Factors of Mobile Banking Usage Behavior - Leo Candra Kirana; Megawati Simanjuntak; Nimmi Zulbainarni (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: The average increase in mobile banking users in Indonesia in the last five years has reached 135.3% per year. The wide diversity of users forms diverse user preferences and intentions, which is a crucial thing for banks to consider. Purpose: The objective of this study is to determine the determinant factors of mobile banking usage behavior using quantitative research and structural equation modeling.Design/methodology/approach: The population of this study is users who have not maximized the use of Bank XYZ mobile banking and used a random sampling technique using the Slovin technique to determine the research sample.Findings/Result: This research contributes to the understanding of consumer behavior concerning technology-based bank products, specifically mobile banking. Findings indicate that PU, PEoU, PR, PC, and personal innovativeness are crucial factors in maximizing mobile banking adoption. This study provides practical strategies for banks, particularly Bank XYZ, to develop policies that enhance these factors, ultimately encouraging mobile banking utilization by improving application design and service quality.Conclusion: This study found significant relationships between all the relationship variables tested which between PU, PEoU, PR and PC to behavioral intention to use mobile banking; and personal innovativeness and behavioral intention to use mobile banking to mobile banking usage behavior.Originality/value (State of the art): This research uses the Technology Acceptance Model (TAM) theory with the addition of PR and PC. Keywords: behavioral intention, digital transaction, mobile banking, perception of customer, usage behavior